Implementasi Metode Tanya Jawab Dalam Meningkatkan Kemahiran Berbicara Siswa Kelas XII Di Madrasah Aliyah Hasyim Asy’ari, Jogoroto, Jombang - Najahah, Umdatun; Qomariyah, Lailatul (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2023)
Abstrak—the primary motivation behind this research stems from the deficiency observed in students' speaking skills. There exists a subset of students who experience fear and embarrassment during the learning process due to their perceived inadequacy in speaking skills. This lack of communication proficiency results in diminished student engagement within the learning journey. Consequently, the researcher intends to address the following inquiries 1. Strategies for enhancing the proficiency of class XII students'